The Proudest Color! - Modir, Sheila; Kashou, Jeff; Mikai, Monica (Reedley, CA : Familius LLC, 2021)
Zahra sees the world in vivid colors. When kids at school tell her shes different because of the color of her skin, she doesnt know how to feel, but her mother tells her to feel proud.
Keywords: Human skin color -- Juvenile fiction; African Americans -- Juvenile fiction; African American girls -- Juvenile fiction; Race -- Juvenile fiction; Racism against Black people -- Juvenile fiction; Identity (Psychology) in children -- Juvenile fiction; Emotions -- Juvenile fiction; Picture books